Identification of Hazards and Risk Assessment in the Workplace of PT. Nusantara Traisser Site PT. Vale Indonesia Sorowako, South Sulawesi - Mahindra, Fahni; Fanani, Yazid; Putri, Fairus Atika Redanto (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
The mining industry has a high risk of accidents, thereby prioritizing the understanding of safety and occupational health aspects. This research discusses the potential hazards and risk values for each work area of Nusantara Traisser Ltd. at the site of Vale Indonesia Pte Ltd. in 2023. Potential hazards came from field observations, and risk assessments were conducted by analyzing the probability, exposure, and consequence values of each identified hazard. These values were then adjusted according to the semi-quantitative risk level standards of William T. Fine. This research employed an observational approach using the AS/NZS 4360:2004 method for risk management. The results of the study indicated that the total number of potential hazards identified in the four work areas was 11, each with its respective risk value. The highest risk level reached 300, classified as priority 1, involving the hazard of mining traffic in the Anoa North Ground Training area (Mines HSOR Department) and the Enggano Coal and Sulfur Storage area. The recommended risk controls for each work area include elimination, engineering control, administration, and personal protective equipment (PPE).